MicroRNA-24-3p regulates neuronal differentiation by controlling hippocalcin expression - Kang, Min-Jeong (Cell Mol Life Sci, 2019)
Hippocalcin (HPCA) is a neuron-specific calcium-binding protein predominantly expressed in the nervous system. In the present study, we demonstrate that HPCA regulates neuronal differentiation in SH-SY5Y cells. We observed that the expression level of HPCA was increased during neuronal differentiation. Depletion of HPCA inhibited both neurite outgrowth and synaptophysin (SYP) expression, whereas overexpression of HPCA enhanced neuronal differentiation. Interestingly, we also found that the expression of HPCA mRNA was modulated by miR-24-3p. Using a dual-luciferase assay, we showed that co-transfection of a plasmid containing the miR-24-3p binding site from the 3′-untranslated region (3′UTR) of the HPCA gene and an miR-24-3p mimic effectively reduced luminescence activity. This effect was abolished when miR-24-3p seed sequences in the 3′UTR of the HPCA gene were mutated. miR-24-3p expression was decreased during differentiation, suggesting that the decreased expression level of miR-24-3p might have upregulated mRNA expression of HPCA. As expected, upregulation of miR-24-3p by an miRNA mimic led to reduced HPCA expression, accompanied by diminished neuronal differentiation. In contrast, downregulation of miR-24-3p by an antisense inhibitor promoted neurite outgrowth as well as levels of SYP expression. Taken together, these results suggest that miR-24-3p is an important miRNA that regulates neuronal differentiation by controlling HPCA expression. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00018-019-03290-3) contains supplementary material, which is available to authorized users.